The Influence of Contextual Teaching and Learning (Ctl) Model on Math Problem Solving Skills in Fractional Material Stories in Elementary School Students: Literature Study: Pengaruh Model Contextual Teaching and Learning (Ctl) Terhadap Kemampuan Pemecahan Masalah Matematika Soal Cerita Materi Pecahan Pada Siswa Kelas IV SD: Studi Literatur - muhammad senjawijaya; Wiwik Okta Susilawati; Riyadi Saputra (Journal of Vocational Education and Information Technology (JVEIT), 2022)
The ability to solve mathematical problems in fraction material in the form of story problems is an issue faced by elementary school students, especially in the fourth-grade students. Analysis, reasoning, and understanding in solving students' story problems are still weak, besides that students assume that learning mathematics is difficult and unpleasant before trying it. This is the research’s background with the aim of knowing the effect of the Contextual Teaching and Learning (CTL) model on the ability to solve mathematical problems in telling fraction material. This research used the Literature Study. Data collection techniques obtained from the study of literature by collecting data and references from a number of books, journals and theses that fit the purpose of the study. The research results obtained in this study by using literature studies are 1) Student learning is more meaningful by linking the material to the real world, 2) Pressing students to be able to exchange knowledge and learn to work together, 3) Give students the ability to solve mathematical problems in the matter of fraction material stories. This research was conducted by comparing arguments, ideas, opinions and research results from 54 references taken by researchers in this study. This shows that there is The Effect of Contextual Teaching and Learning (CTL) Model in Math Problem Solving Ability in Story Fractional Material Story in Grade IV Elementary Students.